Managing Death in the Intensive Care Unit - Curtis, J. Randall (Oxford University Press, 2001)
This volume reviews the state of the art in caring for patients dying in the ICU, focusing on both clinical aspects of managing pain and other symptoms, as well as ethical and societal issues that affect the standards of care received. The book also addresses the changing epidemiology of death in this setting related to managed care, practical skills needed to provide the highest quality of care to terminal patients, communicating with patients and families, the mechanics of withdrawing life-supporting therapies, and the essential role of palliative care.....